Comparative assessment of conventional, conservation, and organic agriculture for productivity and profitability of pigeonpea under pigeonpea(Cajanus cajan)-wheat (Triticum aestivum) system - DAS, T K; SAHA, PRIYANKA; SINGH, RAJ; RAJ, RISHI; MAHANTA, DIBAKAR; BHATIA, ARTI; SHUKLA, LIVLEEN; MEENA, M C; SEN, SUMAN; ROY, ARKAPRAVA; GUNTURI, ALEKHYA; SHARMA, TARUN (The Indian Journal of Agricultural Sciences, 2025)
A study was carried out during 2022–23 and 2023–24 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the impact of conventional agriculture (CT), conservation agriculture (CA), and organic agriculture (OA) on pigeonpea [Cajanus cajan L. (Millsp.)] under pigeonpea-wheat (Triticum aestivum L.) system. Conservation agriculture treatments such as CA1, CA2 and CA3 (zero till permanent narrow bed (CA-PNB), permanent broad bed CA-PBB) and permanent flat bed (CA-PFB), respectively) outperformed CT and OA on growth parameters such as plant height, dry matter accumulation, leaf area index, crop growth rate and relative growth rate of pigeonpea. The pigeonpea variety selected for the experiment was Pusa Arhar 16. The experiment was laid out in a randomized block design (RBD) with 3 replications. Notably, CA2 led to achieve greater plant height (129.3 cm and 132 cm) and dry matter accumulation (1143.7 g/m²) in both years. Enhanced nodulation in CA treatments suggested improved biological nitrogen fixation and soil health. Yield attributes under CA were significantly greater with CA2 treatment, showing the highest pod numbers, grains/pod, and pod weight/plant. Grain yield in CA2 was 24.3–30.5% higher than in CT and 30.1–36.8% higher than in OA3. Economic analysis revealed that the cost of cultivation for CA treatments was marginally higher (8–9%) than CT, but gross returns for CA1, CA2 and CA3 were substantially higher. CA2 gave highest net returns with a 39% and 54% higher than over CT in the first and second years, respectively. Net B:C for CA2 were also superior, showing a 27–40% improvement over CT over the years. It may be concluded that conservation agriculture, particularly CA2, which provides better growth, higher yields and income would be economically superior to conventional and organic agriculture. This as well underscores the potential of CA to enhance pigeonpea productivity and farmers’ income in upper and middle Gangetic plains of India.